Information Technology (IT): Benefits, barriers and concerns of Muslim scholars in Islamic Studies - Yousif, Ahmad (2010)
The information technology (IT) revolution has taken the world by storm. Despite it’s many champions and advocates, IT has left many people feeling confused about its proper place and use. In the Muslim world, attitudes towards IT are quite diverse. On one hand, there are some scholars, particularly those with scientific backgrounds, who eagerly embrace the latest technology with open arms. On the other hand, there are others, particularly those in the Islamic disciplines, who are far more reserved in their receptiveness to such technology. This paper examines the field of IT, in an effort to determine the extent to which such technology can be considered Islamic or non-Islamic. The paper also discusses some of the benefits, barriers and concerns of Muslim societies in general and Muslim scholars in the field of Islamic Studies in particular, for accepting and utilizing IT. Recommendations are made as to how some of these barriers and concerns can be overcome.